Barley (Hordeum vulgare ) circadian clock genes can respond rapidly to temperature in an EARLY FLOWERING 3 -dependent manner. (31st August 2016) - Ford, Brett; Deng, Weiwei; Clausen, Jenni; Oliver, Sandra; Boden, Scott; Hemming, Megan; Trevaskis, Ben
Highlight: In barley, GIGANTEA and the PSEUDO RESPONSE REGULATOR clock genes respond rapidly to temperature in an EARLY FLOWERING 3 -dependent manner. Abstract: An increase in global temperatures will impact future crop yields. In the cereal crops wheat and barley, high temperatures accelerate reproductive development, reducing the number of grains per plant and final grain yield. Despite this relationship between temperature and cereal yield, it is not clear what genes and molecular pathways mediate the developmental response to increased temperatures. The plant circadian clock can respond to changes in temperature and is important for photoperiod-dependent flowering, and so is a potential mechanism controlling temperature responses in cereal crops. This study examines the relationship between temperature, the circadian clock, and the expression of flowering-time genes in barley ( Hordeum vulgare ), a crop model for temperate cereals. Transcript levels of barley core circadian clock genes were assayed over a range of temperatures. Transcript levels of core clock genes CCA1, GI, PRR59, PRR73, PRR95, and LUX are increased at higher temperatures. CCA1 and PRR73 respond rapidly to a decrease in temperature whereas GI and PRR59 respond rapidly to an increase in temperature. The response of GI and the PRR genes to changes in temperature is lost in the elf3 mutant indicating that their response to temperature may be dependent on a functional ELF3 gene.